Personal Experience and Public Support for Internet Shutdowns in Rural India - Garimella, Kiran; Karekurve-Ramachandra, Varun; Collis, Avinash (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
India, despite being the world’s largest democracy, leads the globe in the number of government-imposed internet shutdowns. While internet access is crucial for daily life, there is paradoxically growing public support for these shutdowns. This raises important questions about how individuals form their opinions on internet shutdowns and whether personal experience can alter these beliefs. In this paper, we develop and test an experiential intervention to examine whether personally experiencing an internet shutdown changes individuals’ attitudes toward such policies. We recruited 246 participants from rural India and asked them to voluntarily disconnect from the internet for 48 hours. Our results reveal that contrary to expectations, participants did not show a significant shift in their beliefs. In fact, a slight increase in support for internet shutdowns was observed after the intervention. Qualitative feedback suggests that participants often substituted internet use with offline activities, such as spending time with family or focusing on personal development, which may have contributed to this unexpected outcome. This study highlights the difficulty of changing deeply held beliefs, even when individuals experience firsthand the inconvenience of an internet shutdown. Our findings emphasize the complexity of public opinion on digital rights and governance, suggesting that experiential interventions alone may not be sufficient to shift perspectives. The study contributes to the broader discourse on internet governance and the challenges of addressing public support for internet restrictions.